Kajian Kualitatif Deskriptif tentang Pendidikan Teknologi Informasi dalam Era Digital - Muh. Wahyu Suryandi Adam (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
Information Technology (IT) education has become a crucial component in the global education system in the current digital era. With the rapid development of technology, the world of education has also undergone significant changes, particularly in teaching methodologies. Information Technology is not only seen as a field of study but also as a powerful tool that supports the learning process across various disciplines, including social sciences, science, and humanities. The use of IT in education enables the creation of more interactive, dynamic, and easily accessible learning experiences for people from various backgrounds. This study aims to provide a comprehensive overview of the important role of Information Technology education in improving the quality of education, as well as the challenges and opportunities faced in its implementation. This research adopts a descriptive qualitative approach with a literature study to gather and analyze various relevant sources related to this topic. The data obtained indicate that despite significant challenges, such as the lack of adequate infrastructure and the readiness of educators to use technology, the implementation of IT in education has a significant positive impact on the quality of learning. The implementation of IT opens up great opportunities, particularly in terms of learning accessibility, which can be accessed by anyone, anytime, and anywhere. Technology also provides flexibility in teaching methods, both online and offline, allowing students to learn according to their needs and abilities. On the other hand, the use of IT can enhance the quality of learning through various innovations such as e-learning, simulations, and interactive learning tools that support a deeper and more enjoyable understanding of the material. Therefore, IT has become one of the key elements in advancing the world of education towards a more advanced and inclusive digital era.